Reconsidering Domestic Sale of Goods Remedies in Light of the CISG - Whittington, Nicholas (Victoria University of Wellington Law Review, 2006)
This article suggests that New Zealand should overhaul the remedies available for breach of sale of goods contracts. It argues that the Sale of Goods Act 1908 should be repealed and the principles and provisions of the United Nations Convention on Contracts for the International Sale of Goods 1980 (CISG) should be adopted in its place. This would have the effect of eliminating the unnecessary distinction currently made between domestic and international sale of goods, and finally ridding the law of the condition-warranty distinction which has become out of date and leads to uncertainty and injustice. It is argued that the provisions of the CISG better respond to the transportation and communication costs and distances involved in international sales, considerations which are not insignificant in trade within New Zealand and, consequently, justify a similar approach domestically.